2017
DOI: 10.1093/iwc/iwx013
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Web for People With Upper Body Motor Impairments Using Touch Screen Tablets

Abstract: People with disabilities frequently use the Internet to perform a variety of common activities; however, they may often encounter aggravated accessibility barriers when using mobile devices to access the Web. In order to alleviate the problems faced by this group when using mobile devices, we have extended a previously developed transcoding-based system that adapts nonaccessible web pages to the needs of specific users in order to enhance their accessibility. In this version, we included new adaptation techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The most consistent selection was parameter “font type” (Arial, 67%), while the other two parameters (”font size” and “contrast between background and font”) were within the recommendations for people with dyslexia [20,29,38], even though the selections diverged between participants. Therefore, the results do support existing findings that there is no universal dyslexic web user [8] and that one universal design of a website is not suitable for people with dyslexia [15], because their needs and preferences are too diverse.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The most consistent selection was parameter “font type” (Arial, 67%), while the other two parameters (”font size” and “contrast between background and font”) were within the recommendations for people with dyslexia [20,29,38], even though the selections diverged between participants. Therefore, the results do support existing findings that there is no universal dyslexic web user [8] and that one universal design of a website is not suitable for people with dyslexia [15], because their needs and preferences are too diverse.…”
Section: Resultssupporting
confidence: 71%
“…A customised website could lead to an increase in web accessibility as well as in web usability for people with disabilities [18,22,23], including for people with dyslexia [9,24]. The existing literature shows that a universal design is not appropriate for everyone with dyslexia due to the individual profiles of people with different needs, demands and preferences [15]. Based on this, our study investigated how people with dyslexia react to a customised website that is in accordance with their individual needs and preferences in terms of their usability and suitability and compared their results with the usability and suitability of the default version of a website.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Keates et al [6] detected that users with MIs had to make an additional effort to plan and control physical movements resulting in them being 50% slower than their counterparts without motor disabilities. Other authors also found pointing and clicking actions to be less precise and more time consuming for people with MIs [7]- [17].…”
Section: Introductionmentioning
confidence: 97%